Effect of visceral fat area on prognosis of patients undergoing radical gastrectomy and construction of nomogram - Zhicheng Huang; Baohua Zheng; Zhiwei Wang; Xiaobin Chen; Yu Wang (World Journal of Surgical Oncology)
Abstract Background We aim to investigate the impact of visceral fat area (VFA) on the prognosis of patients following radical gastric resection and develop a nomogram prediction model to forecast the prognosis of gastric cancer patients. Methods We retrospectively analyzed 156 patients who underwent laparoscopic radical gastrectomy for distal gastric cancer in the 900th hospital of the Joint Logistics Support Force from April 2018 to April 2020. We collected the CT image data and clinicopathological data one week prior to the operation and then used software to calculate the VFA, dividing it into two groups: a low VFA group (n = 71) and a high VFA group (n = 85). We compared the clinicopathological characteristics and early postoperative complications of the two groups. The Pearson χ2 test was used to analyze the correlation between body mass index (BMI) and VFA. We used the Kaplan-Meier method to draw the survival curve, analyzed the independent risk factors affecting the prognosis of gastric cancer patients using univariate and multivariate Cox regression models, and established a nomogram model for patient prognosis prediction. Results The results of CT showed that VFA value was (95.89 ± 41.40) cm², and body mass index (BMI) was positively correlated with VFA value (r = 0.291, P < 0.001). The ROC curve shows that VFA can predict the prognosis of patients with gastric cancer significantly better than BMI (AUC = 0.826 vs. AUC = 0.707, P = 0.016). The incidence of incision fat liquefaction, pancreatic fistula, and abdominal infection in the high VFA group was higher than that in the low VFA group (P < 0.05). We followed up with all patients for 0.5–48.5 months, with a median follow-up time of 30 months. We used the Kaplan-Meier method to draw the survival curve. The results showed that the overall survival rate of patients in the high VFA group was significantly higher than that in the low VFA group (χ2 = 38.208, P < 0.001), and the high BMI group was significantly higher than that in the low BMI group (χ2 = 29.767, P < 0.001). Age, the degree of differentiation, complications after surgery, VFA, ASA grading, and TNM staging were all found to have independent effects on the prognosis of gastric cancer patients (Multivariate Cox regression analysis). Multivariate Cox regression analysis led to the construction of a nomogram prediction model for the total survival of gastric cancer patients. Its internal verification C-index was 0.881 (95% CI: 0.852–0.910), and the calibration chart showed good consistency. Conclusions Age, differentiation degree, postoperative complications, VFA, ASA grading, and TNM staging are independent influencing factors for the prognosis of patients with gastric cancer. The constructed nomogram has excellent prediction accuracy and is helpful to evaluate the prognosis of patients.